Veblen in reverse: evidence from the multinational time-use archive - Gershuny, J (Springer, 2009)
This paper explores the historical change in the work-leisure balance using time-diary evidence. Much of the recent discussion of this balance in the developed world has focused on paid work alone. What follows takes a different approach, considering the balance of all work time (paid plus unpaid) against leisure time and observes a tendency over recent decades for leisure to decline relative to work in this broad sense. Much is changing, in employment, family and consumption terms over this period. One possibility is that the relative increase in work time reflects the reversal of the status/leisure gradient: the finacially privileged classes, which once had more leisure than others, now have less. But the paper closes with the speculation that this increase in work time for both men and women may be indirectly conncected with the phenomenon of the women's "dual burden", via an unconsidered but nevertheless important principle of fairness in the distribution of work within households.